Guarantee Yourself and Guarantee The Environment With Seruni 100 cc in Dealing With The Event of Dengue Hemorrhagic Fever in Tangerang District - Meynur Rohmah; Dewi Nur Puspita Sari; Mohamad Yusup Ardawilly; Gaitsa Zahira Shofa (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Dengue fever can appear throughout the year and can affect all age groups. This disease is related to environmental conditions and people's behavior. Community behavior such as the habit of storing water for daily needs such as collecting rainwater, well water, making bathtubs or drums/jars as suitable for breeding mosquitoes. This awareness must be built together so that undesirable things do not happen, one of which is the occurrence of dengue fever. DHF treatment can actually be done in many ways. Starting from the eradication of mosquito nests (PSN) and 3M activities, namely draining, cleaning and stockpiling materials that can hold water. This activity aims to provide counseling and group activity therapy about progressive muscle relaxation techniques for health workers for Covid-19 patients. This is expected to reduce the incidence of dengue fever. The counseling method used leaflets and the provision of 100cc chrysanthemums. After giving the material, participants know and understand the material that has been delivered by the speaker.